Eculizumab safely reverses neurologic impairment and eliminates need for dialysis in severe atypical hemolytic uremic syndrome - Ohanian M; Cable CC; Halka KK (Dove Medical Press, 2011)
Maro Ohanian, Christian Cable, Kathleen HalkaDepartment of Hematology and Oncology, Scott and White Healthcare, The Texas A&M Health Science Center College of Medicine, Temple, TX, USAAbstract: This case report describes how eculizumab reversed neurologic impairment and improved renal damage in severe atypical hemolytic uremic syndrome. A 50-year-old female, after presenting with diarrhea and abdominal pain, developed pancolitis, acute renal failure, and thrombocytopenia. The patient underwent total abdominal colectomy. Pathology confirmed ischemic colitis with scattered mesenteric microthrombi. Due to mental and respiratory decline, she remained intubated. Continuous venovenous hemodialysis was initiated. Renal failure, neurologic changes, hemolysis, thrombotic microangiopathy, and low complement levels all suggested atypical hemolytic uremic syndrome. Eculizumab 900 mg was administered intravenously on hospital day 6 and continued weekly for four doses followed by maintenance therapy. She recovered neurologically and renally after the third dose, and hematologically by the sixth dose. Her recovery has been sustained on long-term eculizumab treatment. In severe atypical hemolytic uremic syndrome, eculizumab safely reverses neurologic impairment and eliminates the need for dialysis. The optimal duration of treatment with eculizumab remains to be determined.Keywords: eculizumab, thrombotic microangiopathy, atypical hemolytic uremic syndrome